Reliability Analysis of PTMG System Operation PT. Pertamina EP. Bunyu Based On Load Loss Probability Index - Rusady, Rendy; Ismit Mado (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
Power plants are equipment used to generate electricity by converting an energy into electrical energy. In power plants, it is necessary to pay attention to the reliability of the generating system in meeting the needs of a load. The reliability of the generating system can be described by the plant reliability index. To pay attention to the reliability of the generating system, an analysis is needed that is used to evaluate the reliability index of the plant, one of which is Loss of Load Probability (LOLP). This study presents the calculation of the LOLP value at the PT Pertamina EP Bunyu PLTMG in 2022. In calculating the LOLP value, namely by using Microsoft Exel and Matrix laboratory simulation. PT Pertamina EP Bunyu PLTMG has 4 generating units with each capacity having a power of 1000 KW. The duration of disruption of the generating unit affects the Forced Outage Rate (FOR) value which will be used to find the probability of each combination of generating units. From this probability value, the LOLP value is obtained. At the PT Pertamina EP Bunyu PLTMG, the LOLP value is 0.00005579646% with an outage probability of 0.0203657079 days/year. While the standard set by PT PLN (Persero) in the 2018-2027 PLN RUPTL of LOLP is smaller than 0.274% or equivalent to a probability of outage of 1 day / year, it can be said that the reliability index of the power plant at PT Pertamina EP Bunyu PLTMG in 2022 is in the reliable category.